Immunoglobulin G from single plasma donor in immune globulin intravenous causes false positive pyrogen test. (May 2019) - Zervos, Clark; Zimmerman, Thomas P.; Willis, Todd; Flexman, Greg; Srivastava, Jyoti; Silverstein, Rebecca; Williams, Melanie; Vandeberg, Pete; Culp, Jennifer L.; Burns, Doug; Barham, Vickie; Durham, Amy; et al.
Abstract: A sudden, unprecedented failure of USP rabbit pyrogen tests for multiple 10% IGIV-C lots prompted a thorough investigation of the root cause for this phenomenon. All microbe-related testing, including Limulus amebocyte lysate test for endotoxin, proved negative, and no deficiencies were discovered in manufacturing. Plasma pool composition analysis revealed that a single plasma donor ("Donor X″) was common to all pyrogenic IGIV-C lots and that as little as one unit of "Donor X″ plasma (in a pool of ∼4500 units) was sufficient to cause IGIV-C lot failure in the USP rabbit pyrogen test. Whole plasma and Protein A-purified IgG from "Donor X″ caused a temperature increase in rabbits; however, all IgG samples tested pyrogen-negative in two in vitro cell-based pyrogen tests. Flow cytometry showed that "Donor X″ IgG bound strongly to rabbit white blood cells (WBC) but minimally to human WBC. Exclusion of "Donor X″ plasma from manufacturing marked the end of IGIV-C lots registering positive in the USP rabbit pyrogen test. This failure of multiple 10% IGIV-C lots to pass the USP rabbit pyrogen test was demonstrated to be due to the highly unusual anti-rabbit-leukocyte specificity of IgG from a single donor.